Matrimonial Typology in the Mongolian Heroic Epic, J̌angγar - AODUNHU (ODONKÜÜ) (Távol-keleti Tanulmányok, 2021)
The Mongolian heroic epic J̌angγar cycles include many independent chapters, which are all connected to the deeds of the king, J̌angγar qaγan and his warriors. N. Poppe, A. S. Kichikov, W. Heissig and Rinčindorǰi studied the structure and pattern of the Mongolian heroic epics and agreed that matrimony is a notable pattern in Mongolian epics. The marriage of Qongγor is a classical story which reflects the typology of matrimony. In this article, I analyse the chapters describing different versions of the marriage of Qongγor in Kalmyk, Mongolia and Xinjiang. In the epic, the hero’s marriage follows the monogamous pattern, and a horse and a knife are presented as signs of engagement. This is evidence of the bride-price system. In addition, the custom of competition for the bride and the exogamy are the most notable features of the matrimonial system described in J̌angγar.